Generation Of Q-Switched Fiber Laser At 1.0-, 1.55-And 2.0-µM Employing A Spent Coffee Ground Based Saturable Absorber - Abdul Latiff, Anas; Mohd Rusdi, Muhammad Farid; Rosol, Ahmad Haziq Aiman; Harun, Sulaiman Wadi; Jafry, Afiq Arif Aminuddin; Kasim, Nabilah; Ab Rahman, Mohd Fauzi; Abdul Khudus, Muhammad Imran Mustafa; Ahmad, Harith (Academic Press Inc., 2021)
Spent coffee ground (SCG) was demonstrated as saturable absorber (SA) for Wideband Q-switched fiber lasers generation. The SCG SA has a broad linear absorption that covers from 1000 nm to 2000 nm wavelength and a modulation depth of 30% at 1.55-µm region. Through purification process, the finer SCG powder is obtained, and be embedded with a polyvinyl alcohol for thin film formation. To realize Q-switching operation lasers, a fabricated SCG film was integrated into three different fiber laser cavities including ytterbium-doped fiber laser, erbium-doped fiber laser, and thulium-doped fiber laser. A peak wavelength has obtainable at 1031 nm, 1563 nm, and 1976 nm for 1-, 1.55-, and 2- µm regions, respectively. The shortest pulse width of 4.80 µs and maximum pulse energy of 0.152 µJ are observed from the YDFL cavity. RF spectrum shows the signal-to-noise ratio for all regions is above 35 dB, indicates a stable pulsing generation. Our technique opens the door for unlimited materials SA from environmentally friendly resources which contribute to sustainable effort.